"With every pair of hands, I get a free brain": An interview with Professor John Bessant. Issue 9 (5th August 2014) - Totterdill, Peter
Abstract : Purpose: – This paper aims to discuss the interview held with Professor John Bessant conducted by Professor Peter Totterdill. John Bessant has been active in research, teaching and consultancy in technology and innovation management for over 25 years. He currently holds the Chair in Innovation and Entrepreneurship at Exeter University where he is also Research Director. Design/methodology/approach: – This wide-ranging and insightful interview looks at the challenges of implementing workplace innovation and the realities involved in the process. It covers questions concerning the importance of innovation to businesses coming out of recession and the relationship between employee involvement and innovation. Findings: – Professor Bessant also discusses the challenge of releasing individual potential and how to harness random creativity. He looks at the "starter conditions" for workplace innovation as well as the factors that mitigate against sustaining it. Practical implications: – Key to sustaining workplace innovation, he argues, are a number of elements including momentum, self-belief and confidence, appropriate resource, leadership and empowerment. In addition, the implementation of workplace innovation does not occur as one big hit but a series of small steps which evolve and develop. Originality/value: – New technology via intranets and social media also help to mobilise a lot more participation. Technology now provides the potential to reach every employee and their involvement can be instantaneous. This can create a notion of shared creativity, the Facebook process of "good idea, I like that, why don't you try that?"